2010
DOI: 10.1017/s1368980010001539
|View full text |Cite
|
Sign up to set email alerts
|

Infant feeding practices among HIV-positive women in Dar es Salaam, Tanzania, indicate a need for more intensive infant feeding counselling

Abstract: Objective To assess feeding practices of infants born to HIV-positive women in Dar es Salaam, Tanzania. These data then served as a proxy to evaluate the adequacy of current infant feeding counselling. Design A cross-sectional survey of infant feeding behaviours. Setting Four clinics in greater Dar es Salaam in early 2008. Subjects A total of 196 HIV-positive mothers of children aged 6–10 months recruited from HIV clinics. Results Initiation of breastfeeding was reported by 95·4% of survey participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 30 publications
2
27
1
2
Order By: Relevance
“…Undoubtedly, this is related to the new revised national policy in favour of breastfeeding for HIV exposed infants when all the conditions (acceptable, feasible, affordable, sustainable and safe) were not fulfilled for artificial feeding. However, our rate is lower than that reported in Tanzania in 2008 in four urban health facilities including two hospitals, where among 196 HIV positive mothers, 187 (95.4%) opted for breastfeeding [7]. Thus, thanks to new revised national policies which strongly promote breastfeeding, it is the preferred option for the majority of HIV positive mothers in Sub-Saharan Africa.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Undoubtedly, this is related to the new revised national policy in favour of breastfeeding for HIV exposed infants when all the conditions (acceptable, feasible, affordable, sustainable and safe) were not fulfilled for artificial feeding. However, our rate is lower than that reported in Tanzania in 2008 in four urban health facilities including two hospitals, where among 196 HIV positive mothers, 187 (95.4%) opted for breastfeeding [7]. Thus, thanks to new revised national policies which strongly promote breastfeeding, it is the preferred option for the majority of HIV positive mothers in Sub-Saharan Africa.…”
Section: Discussioncontrasting
confidence: 73%
“…Thus, mixed feeding is widespread in Africa among HIV positive and negative women. Hurdles to exclusive breastfeeding include: lack of support from the community, beliefs that exclusive breastfeeding is inappropriate, and that maternal milk is insufficient for the child's optimal growth [7]. Yet, early introduction of supplementary food and decrease of maternal milk intake could increase the risk of HIV transmission due to possible lesions of digestive mucous which is still immature in infants below six months of age.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it likely would be beneficial for all counselors to have standardized counseling materials, similar to what the Tanzanian Ministry of Health has adopted for infant feeding counseling in the context of HIV/AIDS (176). Such materials may help to mitigate some of the frustration, confusion, and misinformation that accompanies implementation of changes in guidelines (177).…”
Section: Infant Feeding and Hiv 233mentioning
confidence: 99%
“…The guidelines continue to highlight the importance of avoiding mixed feeding to reduce the risk of HIV transmission and to avoid diarrhoea and malnutrition, although difficulties have been reported in some resource-poor settings (5) and where some mothers have been reported to prefer exclusive formula feeding regardless of the promotion of exclusive breastfeeding (6). Despite its recognised importance, exclusive breastfeeding is not widely practiced in the developing world (7); although a study conducted among HIV-positive mothers in Tanzania showed greater duration of exclusive breastfeeding, the results fail short of national and international recommendations (8). Factors such as the level of education, knowledge of exclusive breastfeeding in relation to PMTCT, the number of infant feeding counselling sessions attended and initiation of breastfeeding within 1 h of giving birth impact exclusive breastfeeding practice in some settings of the sub-Saharan Africa (9).…”
Section: Introductionmentioning
confidence: 99%